Onychomycosis by Syncephalastrum racemosum: case report from Kerala, India - Sabitha Baby; T.G. Ramya; R.K. Geetha (PAGEPress Publications, 2015)
We report a rare case of onychomycosis caused by Syncephalastrum racemosum in a 50-year-old diabetic patient. The patient's nail was surgically excised and thorough debridement was done. The patient was successfully treated with topical nystatin.